Reproductive number - Chaharborj, S. Seddighi; Abu Bakar, Mohd Rizam; Abu Hassan, Malik; Alli, V. (Hikari, 2009)
In this article we want to find the reproductive number, R0, for the three models with a simple method. With this simple method we can find the reproductive number for all of models.